(untitled) (Bangladesh Critical Care Journal, 2014)
Background and aim: Although co-morbidity of childhood diarrhea and severe malnutrition is very common with high mortality, data on predicting factors for deaths in diarrheal under-five children also having severe malnutrition are very limited in medical literature. The aim of this study was to evaluate the clinical predicting factors for death in diarrheal under-five children with severe malnutrition. Methods: The study was designed as a prospective analysis from retrospective data of diarrheal children (case control design) which were collected from electronic database of the hospital of the International Center for Diarrheal Disease Research, Bangladesh (icddr,b) from mid-September 2011 to mid-September 2012. The cases were severely malnourished diarrheal children under the age of five years who died in the intensive care unit and the controls were those who survived. Comparison of clinical characteristics among the cases and the controls were made. Results: There were 32 cases from the ICU and 1790 controls including 253 from the ICU. The median (inter-quartile range) age (months) of the cases compared to the controls was significantly lower [8.0 (4.1, 14.1) vs. 10.0 (6.1, 17.2); p=0.050]. The cases more often had pneumonia (OR 3.40, 95% CI 1.48-7.66, p<0.001) with respiratory distress (OR 30.06, 95% CI 11.47-77.67, p<0.001), frequently presented with the features of clinical sepsis (OR 52.22, 95% CI 24.02-127.68; p<0.001), less often received Oral Rehydration Salt (ORS) at home (OR 0.07, 95% CI 0.03-0.14; p<0.001), and more often had lower Z-score for weight for age [(mean -5.42 ± standard deviation 1.35) vs. (mean -4.14 ± standard deviation 1.28); p<0.001] compared the controls. Conclusion: The brief results of the data suggest that severely malnourished diarrheal children presenting with younger age with a history of lack of intake of ORS at home, extreme under-weight, pneumonia with respiratory distress or clinical sepsis are at higher risk of death. This re-emphasizes the importance of identification of these simple clinical parameters which may help in early aggressive management of these children and underscores the importance of the requirement of extensive mass media education in encouraging the adequate intake of ORS during diarrhea in order to reduce their morbidity and deaths. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19953 Bangladesh Crit Care J March 2014; 2 (1): 25-27